CALPHAD-aided synthesis and characterization of an Al–Co–Cr–Fe–Ni–W high-entropy alloy prepared by arc melting and spark plasma sintering - L. Fenocchio; A. Saviot; S. Gambaro; S. Le Gallet; F. Valenza; M.R. Ardigo-Besnard; G. Cacciamani (Journal of Materials Research and Technology)
In the present work, the novel Al0.15CoCrFeNiW0.15 High-Entropy Alloy (HEA) has been designed by CALPHAD (CALculation of PHAse Diagrams) computations with the in-house built Genova High-Entropy Alloys (GHEA) database, aiming to a mostly monophasic face-centered cubic (FCC) alloy strengthened by the precipitation of secondary μ phase. To explore different preparation routes, alloy samples have been synthesized by both arc melting (AM) and spark plasma sintering (SPS). Samples were characterized by low optical microscopy (LOM), scanning and transmission electron microscopy (SEM and TEM), X-ray diffraction (XRD), and microhardness measurements. Long-term annealing at 1100 °C has been performed, followed by quenching or furnace cooling. AM as-cast sample showed a monophasic FCC microstructure, characterized by large grains. Precipitation of μ phase was observed in the equilibrated and quenched sample, in good agreement with the thermodynamic calculations. On the other hand, SPS samples resulted in a finer microstructure, characterized by the presence of small particles of Al2O3 and μ phase, already present before annealing. Contrary to the thermodynamic predictions, after equilibration and quenching, the dissolution of the μ phase was observed due to the Gibbs-Thomson effect, which enhanced W solubility in the FCC solid solution. Annealing of the SPSed alloy followed by furnace cooling, however, allowed the precipitation of μ, thanks to the slower cooling rate. Overall, this study highlighted CALPHAD's utility for composition selection in complex multicomponent systems and demonstrated how AM and SPS lead to significantly different microstructures and properties, with grain size playing a key role in determining the alloy performances.